High‐Throughput Tumor‐on‐a‐Chip Platform to Study Tumor–Stroma Interactions and Drug Pharmacokinetics. Issue 21 (23rd September 2020) - Chi, Chun‐Wei; Lao, Yeh‐Hsing; Ahmed, A. H. Rezwanuddin; Benoy, Elizabeth C.; Li, Chenghai; Dereli‐Korkut, Zeynep; Fu, Bingmei M.; Leong, Kam W.; Wang, Sihong
Abstract: Drug screening in oncology, especially for triple‐negative breast cancer (TNBC), has high demand but remains unsatisfactory. Currently available models are either nonrepresentative of the complex tumor microenvironment or only suitable for low throughput screening, resulting in a low‐yield success for drug development. To tackle these issues, the L‐ TumorChip system is developed in this study. It is a three‐layered microfluidic tumor‐on‐a‐chip platform integrating tumor microvasculature and tumor–stromal microenvironment with high throughput screening capability. Its layered and modular design is readily scalable through simple integration of multiple units. Here, L‐ TumorChip is validated with a TNBC model. The L ‐TumorChip system emulates certain tumor–stroma complexities and tumor–endothelium interactions, including TNBC invasion through the leaky microvasculature and angiogenesis. Additionally, with this L ‐TumorChip, the influence of different stromal cells, including normal fibroblasts, mesenchymal stem cells, and cancer‐associated fibroblasts (CAF), on cancer cell growth as well as the stromal effects on drug responses to doxorubicin treatment is investigated. The presence of CAF delays drug pharmacokinetics, while apoptotic responses indicated by caspase‐3 activities are higher in coculture with normal fibroblasts. Collectively, the L ‐TumorChip system represents a translational high‐throughput screening toolkit that enables drug screening with a scenario closer to the in vivo conditions. This potential use may therefore facilitate development of new cancer drugs. Abstract : A microfluidic tumor‐on‐a‐chip with integration of tumor–microvasculature and tumorous–stromal microenvironment offers a more representative model to study the cell interactions within the tumor microenvironment and between tumor and the endothelium barrier. This platform enables more precise high throughput drug screening and drug pharmacokinetic studies.